On‐Farm Demonstration and Economic Evaluation of an IoT Sensing System for Irrigation Management in South Carolina - J. O. Payero; U. Sekaran; D. B. Turner; S. Selvalakshmi; M. W. Marshall; N. Smith; J. Croft; A. S. Hill; R. Hitchcock‐Davis (Irrigation and Drainage, 2026)
Irrigation can strongly influence agricultural productivity and sustainability. While sensor‐based irrigation has the potential to improve yield, reduce input costs and enhance resource‐use efficiency, its adoption in commercial agriculture remains limited. This study evaluated and demonstrated the performance of an IoT soil water monitoring system and the effects of sensor‐based irrigation on crop yield and economic returns in commercial farms in South Carolina. Field demonstrations were conducted across 18 site‐year observations (six farms annually from 2020–2022) under centre pivot systems. The centre pivot fields for each farm were divided into sensor fields and companion fields. The sensor fields used soil water potential (SWP) data from sensors installed at multiple depths to guide irrigation, while irrigation in the companion field followed farmers' preferred practices. Data collected from each site included irrigation applied, pumping characteristics, energy use, yield and economic returns. The IoT monitoring system reliably collected and transmitted data across all locations and years. Despite variability, the sensor fields achieved average increases of 11% in yield and 12% in net economic return compared with companion fields. These results indicate that sensor‐based irrigation improves water management and profitability under commercial conditions, supporting broader adoption of these technologies.